PCR based molecular detection of M. tuberculosis and comparison of its efficacy against AFB based bacteriological detection in diagnosis of Pulmonary Tuberculosis in Nepal - Karmacharya, D; Shrestha, L; Bajracharya, B; Dulal, P; Shrestha, S; Dixit, SM (Journal of Institute of Medicine Nepal, 2012)
No abstract available Journal of Institute of Medicine, 2011: 33:1